ANATOMIK TERMINOLOGIYADA LOTIN TILINING XALQARO AHAMIYATI VA ZAMONAVIY TIBBIYOTDAGI ROLI: GLOBAL YONDASHUV (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the international significance of the Latin language in anatomical terminology and its role in modern medicine from a global perspective. The historical development of Latin as the foundational language of anatomy and its function in ensuring standardization through Terminologia Anatomica are discussed. The study highlights the importance of Latin in providing accuracy, consistency, and clarity in anatomical nomenclature, thereby facilitating effective international scientific communication. Furthermore, the role of Latin in modern medical education, clinical practice, and global medical cooperation is examined. The article emphasizes that Latin remains a universal professional language that supports integration, knowledge exchange, and standardization in contemporary global medicine.